2008
DOI: 10.1088/0022-3727/41/24/245403
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cadmium doped zinc oxide (Cd : ZnO) thin films prepared by spray pyrolysis method

Abstract: Thin films of cadmium doped zinc oxide (Cd : ZnO) with different cadmium concentrations have been prepared by the spray pyrolysis method on different substrates at 400 °C. The physical properties of the films were studied as a function of increasing cadmium dopant concentration (up to 25 wt%). The films were characterized by different methods to understand their structural, optical and electrical properties. Energy dispersive x-ray diffraction spectroscopy analysis showed that the Cd concentration in the solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 34 publications
5
46
0
1
Order By: Relevance
“…This emission, also explained by the first principle study of native point defects in ZnO, may be due to oxygen anti-site defects [23]. Recently, S. Vijayalakhmi et al [20] reported that the near band edge emission peak vanished at 25 % Cd doping, but in the present study NBE peaks with low intensity have been clearly observed.…”
Section: Photoluminescencesupporting
confidence: 51%
See 1 more Smart Citation
“…This emission, also explained by the first principle study of native point defects in ZnO, may be due to oxygen anti-site defects [23]. Recently, S. Vijayalakhmi et al [20] reported that the near band edge emission peak vanished at 25 % Cd doping, but in the present study NBE peaks with low intensity have been clearly observed.…”
Section: Photoluminescencesupporting
confidence: 51%
“…Broad low intense shoulder is observed at 650 nm. This hump of low intensity may be due to oxygen vacancy created during the growth of the samples [20]. From Fig.…”
Section: Photoluminescencementioning
confidence: 89%
“…Variations in crystallite size with doping concentration may be explained in a number of ways: First, the decrease in crystallite size could be due to an increase in number of Cd atoms, which would exert drag forces on boundary motion and grain growth. Second, the increase in the number of dopant atoms may lead to increased numbers of point defects, which would give rise to higher grain boundary mobility and grain growth rates [1,34].…”
Section: International Letters Of Chemistry Physics and Astronomy Vomentioning
confidence: 99%
“…The spray pyrolysis method is used for preparing large numbers of pure and doped thin films because the method is simple, inexpensive, and easy to apply for growing uniform films and allows the coating of large areas [1,24]. This work aims to study the effects of doping concentration and annealing on the structural, morphological, and optical properties of Cd-doped ZnO thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The ZnO (hexagonal) and CdO (cubic) have very different crystal structure, and also, low thermodynamic solubility (~ 2 mol.%) of CdO in CdO-ZnO system make it very difficult to grow single-phase hexagonal Cd x Zn 1−x O thin films with high Cd concentration (Ishihara et al 2006). Different methods can be employed to grow mixed Cd x Zn 1−x O thin films, such as molecular beam epitaxy (Wang et al 2006), sputtering (Ma et al 2011), pulsed laser deposition (Makino et al 2013) and spray pyrolysis (Vijayalakshmi et al 2008). Compared to different methods, the spray pyrolysis method is simplest industrially applicable method to produce metal oxide thin films.…”
Section: Introductionmentioning
confidence: 99%